Saturated high repetition rate soft x-ray lasers - Wang, Yong, author; Rocca, Jorge, advisor (Colorado State University. Libraries, 2007)
This dissertation resulted in the demonstration of tabletop soft x-ray lasers operating at 5 Hz repetition rate with average powers of 1-5 μW in numerous transition of the 4d1S0-4p1P1 nickel-like and the 3P1S0-3S1P1 neon-like ion isolectronic sequences with wavelengths ranging from 32.6 nm to 13.2 nm. The lasers operate in the gain-saturate regime necessary for efficient laser energy generation. Lasing at shorter wavelengths was also observed in transitions of the same nickel-like ion isolectronic sequence, with amplification in the 11.9 nm line of nickel-like Sn approaching gain saturation, and progressively reduced gain for wavelengths as low as 10.9 nm for nickel-like Te. The results were obtained by heating plasmas of selected materials with picosecond duration optical laser pulses of only 1J energy impinging at grazing incidence angles optimized for maximum energy deposition. The grazing incidence pumping geometry takes advantage of the pump beam refraction into the plasma to efficiently deposit a large fraction of its energy into a pre-selected plasma region with optimum electron density for amplification. The soft x-ray lasers were characterized in term of small signal gain, output pulse energy, pulse duration, beam divergence, and spatial coherence. Streak camera measurements for the 13.9 nm nickel-like Ag and 13.2 nm nickel-like Cd laser showed that the laser pulses have a duration of about 5 ps. To further improve the characteristics of these high repetition rate table-top soft x-ray lasers in terms of peak spectral brightness, short pulse duration, defined polarization, and spatial coherence, we investigated the seeding of the soft x-ray amplifiers with high harmonic pulses generated in a gas cell using the same pump laser. Amplification of pulses from the 25th harmonic pulses of the Ti:sapphire laser in a 32.6 nm line of Ne-like Ti laser amplifier by nearly two orders of magnitude was demonstrated to generate highly monochromatic laser pulses that were measured to approach full spatial coherence. Based on experimental measurements of the main parameters of the seeded soft x-ray laser pulses the peak spectral brightness is estimated to be ~ 2x10 26 photons/(s mm2 mrad2 0.01% bandwidth). This scheme for the generation of sub-picosecond soft x-ray laser pulses should be scalable to produce extremely bright lasers at very short wavelength. These high repetition rate short wavelength lasers will make possible a variety of new studies of surfaces and materials, and enable the development of unique metrology and processing tools for industry. As an example of the potential of these compact lasers as intense sources of soft x-ray light for applications the nickel-like cadmium and silver lasers were used as illumination sources in a table-top high resolution microscope that achieved a spatial resolution better than 38 nm.
Keywords: optics